REKONSTRUKSI MODEL PENYULUHAN PERTANIAN DAN KEHUTANAN BERBASIS PENGELOLAAN DAERAH ALIRAN SUNGAI TERPADU [STUDI KASUS DI TIGA DESA DI WILAYAH KABUPATEN MALANG] Reconstruction Of Integrated-Watershed-Management-Based Agricultural And Forestry Extensions [A Case Study in Three Villages in the Area of Malang Regency] - Sugiyanto Sugiyanto (Lambung Mangkurat University-Indonesia, 2014)
This study tried to discover integrated-watershed-management-based extension model with embedded case study research approach. FEATI (Farmer Empowerment Throught Agricultural Technology And Information) Program is an extension program based on farmers’ needs by considering the environment which is managed independently from by, and for farmers, which takes place in many areas, including Malang Regency. The study result showed the integration of extension approach in identifying farmers’ necessities of life by the process of extension, establishing reward and punishment which supported change in behaviors in managing watershed had been conducted effectively. The utilization of watershed for agricultural activities supported by the use of appropriate technologies, presence of correct institutions for reconstruction process through socialization, externalization, combination and internalization managed to change farmers’ behaviors in terms of knowledge, skills, and attitudes in integrated-watershed-management-based farming. Meanwhile, farmers’ independence in farming was strongly determined by their capacity in selecting materials, sources and accommodative learning participants. Aspects of suitability of material, intellects and routine coaching created significant improvement in the change of farmers’ behaviors in watershed-management-based farming.Keywords: Integrated extension, FEATI program and Farmers’ independence.